Teaching Staff and Student Perceptions of Staff Support for Student Mental Health: A University Case Study - Helen Payne (MDPI AG, 2022)
Background: There are significant concerns for student mental health in higher education. New factors affect student mental health, and campus counselling services are overwhelmed. Struggling students turn to ideally placed familiar teaching staff for support. This qualitative study, conducted in an East of England university, aimed to explore student and staff perceptions of support offered by teaching staff to students grappling with their mental health. It is unique, combining both staff and student perceptions, many of which overlapped. Methods: A thematic analysis was conducted of in-depth, semi-structured interviews with a small number of self-selecting staff/students. Findings (results): Staff felt inadequate in several aspects, and students agreed to give useful suggestions for their preferred support. Conclusions: It was cautiously established that staff training in mental health literacy (knowledge, skills, attributes, and understanding) was required. Specific training was recommended in pastoral care for personal tutors and for staff pedagogy on health professional programmes. Finally, teaching staff needed support when supporting students with poor mental health. Such training and support can be integrated into a preventative, university-wide, holistic policy for student mental health commensurate with the University Mental Health Charter. Embedding such supportive practice into the curriculum is preferable to add-on services and/or interventions.